Number talks: Comparative insight into undergraduate and graduate student literacy - Peni, Nur Robiah Nofikusumawati; Pratiwi, Septia Ayu; Prabowo, Anggit (Universitas Papua, 2024)
Variations in competence and confidence among higher education students in mathematical literacy, numeracy, and logical thinking are crucial for developing critical reasoning, problem-solving skills, and the application of quantitative knowledge in both academic and real-world contexts. However, limited research has explored how students from different academic disciplines vary in their competence, confidence, and challenges related to these fundamental areas. This gap in the literature highlights the need for a comprehensive examination of such variations across diverse higher education fields. This study aims to compare the levels of mathematical literacy, numeracy, and logical thinking among university students, focusing on their knowledge, confidence, and the challenges they face. A comprehensive survey was employed, covering several dimensions of mathematical literacy, such as real-world applications of mathematics, numeracy comprehension, numerical self-confidence, and the role of emotions in logical thinking. Drawing on responses from Indonesian university students, the study reveals that students generally perceive their abilities as moderate to good, though significant differences are evident across academic disciplines and levels of study. A notable correlation was found between the focus of students' academic programs and their mathematics literacy, with certain disciplines demonstrating higher competency levels. The findings highlight the importance of integrating practical applications and emotional intelligence into mathematics education to foster greater confidence, knowledge, and engagement. This research contributes valuable insights into mathematical literacy and proposes new strategies to improve teaching practices and curricula. The comparative analysis offers a broader perspective, essential for shaping future assessments in mathematics, logical reasoning, and numeracy literacy.